A Systematic Review of the Valproic-Acid-Induced Rodent Model of Autism. - Chaliha, Devahuti; Albrecht, Matthew; Vaccarezza, Mauro; Takechi, Ryu; Lam, Virginie; Al-Salami, Hani; Mamo, John (2020)
Autism spectrum disorder (ASD) is a neurodevelopmental disorder characterised by repetitive behaviours, cognitive rigidity/inflexibility, and social-affective impairment. Unfortunately, few pharmacological treatments exist to alleviate these socio-behavioural impairments. Prenatal administration of valproic acid (VPA) has become an accepted animal model of ASD and has been extensively used to explore new pharmacotherapies in rodents. We conducted a systematic review of the behavioural impairments induced by the VPA model in rodents, with specific reference to 3 core socio-behavioural alterations associated with ASD: repetitive behaviours, cognitive rigidity/inflexibility, and social-affective impairment. We systematically reviewed studies attempting to alleviate these core behavioural alterations using pharmacological means. We include 132 studies exploring the prenatal effects of VPA in rodents. Gestational exposure to VPA in rodents has significant effects on rodent-equivalent measures of the 3 core behavioural traits characteristic of ASD in humans, inducing social impairments, repetitive behaviour, and cognitive rigidity/inflexibility after birth. This model's validity has seen it used to test potential drug treatments for ASD and is likely to continue doing so. We conclude the rodent VPA model may be suitable to examine future therapeutic interventions for ASD, providing an overview of the progress made so far.